Influence of Si/Al molar ratio on the hydrogenation, isomerization and ring opening of naphthalene over silica-alumina supported Ni2P catalyst. (1st August 2018) - Cui, Sha; Wang, Genggeng; Yang, Ying; Liu, Baijun
Abstract: Ni2 P catalysts supported on amorphous silica-alumina (ASA) with various Si/Al molar ratios (n) of ∞, 3.40, 1.28, 0.57, 0.21, 0.10 and 0, were prepared using a co-impregnation method followed by temperature-programmed reduction. The resultant Ni2 P/ASA-n catalysts were characterized by means of X-ray diffraction (XRD), N2 adsorption and desorption, transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), temperature-programmed ammonia desorption (NH3 -TPD) and FTIR spectroscopy of adsorbed pyridine (Py-IR). The catalytic properties were tested towards naphthalene hydrogenation, isomerization and ring opening in a fixed bed reactor under the following reaction conditions of P  = 4 MPa, LHSV  = 3 h −1, H2 /oil = 600 volume ratio and T  = 360 °C. It is found that the superior naphthalene hydrogenation ability was obtained over the Ni2 P/ASA-0.57 catalyst, while higher isomerization and ring opening activity were achieved using Ni2 P/ASA-0.21 as the catalyst. It is concluded that the high naphthalene hydrogenation capacity is relevant to the small Ni2 P particle size and the isomerization and ring opening activity mainly depends on the acid amount of catalyst.